2011
DOI: 10.1007/s12206-011-0808-y
|View full text |Cite
|
Sign up to set email alerts
|

Electrode layout of ZnO pyroelectric sensors

Abstract: In the present study, an electrode layout of pyroelectric sensors is developed to improve electric signals. Voltage responsivity is a main target to enhance the performance of pyroelectric sensors. A partially covered, top electrode has been proven to effectively increase the voltage responsivity of pyroelectric sensors. In the experimental results, the proposed electrode layout with an array type in ZnO pyroelectric sensors possessed higher voltage signals, about 3.6 times that of a fully covered type, and ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…This frequency is considerably higher than conventional PVDF sensors, which typically exhibit a decay below 100 Hz . The f 3dB frequency is also higher than that in recent works demonstrating improved response times (f 3dB ∼ 300 Hz) in pyroelectric sensors with patterned top electrodes, suggesting that the IR transparency of graphene is indeed having an effect on detector performance.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…This frequency is considerably higher than conventional PVDF sensors, which typically exhibit a decay below 100 Hz . The f 3dB frequency is also higher than that in recent works demonstrating improved response times (f 3dB ∼ 300 Hz) in pyroelectric sensors with patterned top electrodes, suggesting that the IR transparency of graphene is indeed having an effect on detector performance.…”
mentioning
confidence: 64%
“…It has been demonstrated that patterning the top electrode enhances response time by allowing a portion of incident radiation to be directly absorbed by the pyroelectric. However, this comes at the expense of effective detector area since those regions are no longer electrically connected . A trade‐off thus arises between having sufficient metalized area for signal capture, and having sufficient exposed pyroelectric surface for improved frequency response.…”
mentioning
confidence: 99%
“…Appropriately designing the parameters of the substrate, membrane layer, electrodes and pyroelectric layer could increase the temperature variation rate, thereby effectively improving the performance of the device. By studying the influence of the electrode layout on the performance of pyroelectric detectors, Hsiao and coauthor showed that ZnObased pyroelectric sensors with a partially covered electrode (PCE) layout in an array type possessed higher voltage signals, about 3.6 times that of a fully covered type [51]. Then, PCEs in comb-like form were introduced to further improve the voltage responsivity by 900% relative to those with fully covered electrodes (FCE) at a low frequency, as shown in figure 3 [45].…”
Section: Zno-based Pyroelectric Pdsmentioning
confidence: 99%